Ethnomathematical Study on Cultural Artifacts: An Ethnographic Field to Classroom Practice - Pradhan, Jaya Bishnu (Journal of Mathematics Education, 2023)
The implicit mathematical ideas, practices, and experiences in the everyday life of children outside the classroom could be a powerful and interesting pedagogical tool to communicate formal mathematical concepts. The main objective of this study is to explore the ethnomathematical ideas embedded in the cultural artifacts and assess their contribution to the process of teaching and learning of school mathematics. The methodological procedures include in-depth interviews and observation of students and teachers regarding mathematical ideas comprised in cultural artifacts at different moments. The mathematical knowledge hidden in the various cultural artifacts has been analyzed based on written documents, photographs, and video graphs. The findings indicated that the cultural artifacts provide an ample opportunity to understand different mathematical concepts. In addition, students have wonderful learning experiences beyond the four walls of the classroom and connect ethnomathematical ideas to conceptualize formal mathematics